120 Who does singlepoint serve?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Chumbley, Karen; Tempest, Emma; Rowe, Frances; Sheldon, Joanne; Davies, Kathryn
Abstract : All patients should have equitable access to palliative care services according to need. A service evaluation to determine who is using a 24 hour single point of access helpline. Background: Many palliative care services have systems to improve care co-ordination and access to palliative care and end of life support. St Helena Hospice developed a single point of access (SinglePoint), rapid response nursing service and an Electronic Palliative Care Coordination System (EPaCCS) called the 'My Care Choices Register'. We evaluated if this service is accessed by the population hospices traditionally serve or it widens access for those with previously unmet need. Aim: To assess if the demographics of service users reflect those of the population it serves and thus identify groups under utilising the service. Design: A service evaluation looking retrospectively at calls to SinglePoint in September 2016. Setting/participants: Calls to SinglePoint in September 2016 related to 321 individuals. Results: 19% of calls concerned patients under 65 years old, 23% were 65–74, 35% were 75–84 and 23% were 85 or over. 54% of calls concerned female patients. 44% of calls were from Colchester district, 51% from Tendring district and 5% from Mid Essex district. 73% of calls concerned patients with a cancer diagnosis. 15% of patients were living in care homes. 49% of patients were already known to the hospice. Conclusion: Key groups under using the service included people with non-cancer diagnoses and those from areas of deprivation. Further work about care home residents and the elderly is needed to define why their utilisation of the service is low. Undertaking a service evaluation of this sort is helpful in guiding future efforts to target areas of unmet need.